Strategi Dinas Komunikasi dan Informatika Kabupaten Ciamis dalam Meningkatkan Layanan Informasi Publik Melalui Aplikasi Helo Ciamis - Devi Karina Seviany; Irfan Nursetiawan; Dini Yuliani (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
Amidst the challenges of digital literacy and information reach, this research examines the strategy of the Communication and Informatics Office (Diskominfo) of Ciamis Regency in enhancing public information services through the Helo Ciamis application in 2024. The primary underlying issue is the lack of socialization and digital literacy concerning the application's use. The study's objective is to describe Diskominfo Ciamis's strategy for improving public information services via the Helo Ciamis application. This research adopts a descriptive qualitative method, with data collected through literature review, structured interviews, and observation. The findings indicate that the implementation of Diskominfo Ciamis's strategy to enhance public information services through Helo Ciamis has not yet been optimal. Key obstacles include limited resources, insufficiently solid coordination, varying challenges in community digital literacy, evolving cyber threats, and the absence of structured user feedback mechanisms. To address these, Diskominfo has undertaken efforts such as budget adjustments, human resource capacity building, strengthening cross-sectoral coordination, implementing strict Standard Operating Procedures (SOPs), and developing direct feedback features within the application. The implications of this research highlight the importance of a comprehensive strategy that addresses socialization, capacity building, and feedback mechanisms for the optimization of digital public information services.